Learn Lua for iOS Game Development - Varma, Jayant. (Apress : Imprint: Apress, 2013)
So you have a great game idea for iPhone or iPad, but Objective-C just seems a bit daunting. What are your alternatives? The App Store is very picky about languages, but there is hope: Lua is a versatile, lightweight, fast, and easy to learn language that you can use to build your iOS games and get them accepted into the App Store. Learn Lua for iOS Game Development walks you through the Lua basics, then shows you how to create games using the top Lua frameworks like Corona SDK, Gideros, Moai, and even how to create games on the iPad (not just for the iPad) with Codea. You aren't tied to Xcode and Objective-C -- you can create all sorts of amazing games with Lua. But if you already have an existing iOS game, you'll also learn how to integrate Lua to extend the game. If you're an aspiring or current iOS developer, you need to know Lua, and Learn Lua for iOS Game Development will give you just what you need to do that.